Adults' and children's perception of facial expressions is influenced by body postures even for dynamic stimuli. Issue 4 (3rd July 2017) - Nelson, Nicole L.; Mondloch, Catherine J.
ABSTRACT: A growing literature shows that body postures influence recognition of static facial expressions; a fearful face, for example, is perceived as angry when presented on an angry body posture. In daily life, however, people conveying emotions are moving. Here we provide the first examination of such congruency effects for stimuli with naturalistic movement. Adults and children were asked to label the facial expression in static or dynamic whole-person displays comprising congruent (e.g., sad face on sad body) and incongruent (e.g., sad face on fearful body) expressions. Recognition was impaired on incongruent trials, especially for dynamic stimuli and despite eye-tracking data confirming that both age groups attended to the face, as instructed. Our findings highlight the importance of integrating whole-person and dynamic stimuli into research and theories of emotion perception.